2015
DOI: 10.1108/aaaj-04-2012-01007
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy, accountability and impression management in NGOs: the Indian Ocean tsunami

Abstract: Purpose – Prior research has investigated legitimation strategies in corporate annual reports in the for-profit sector. The purpose of this paper is to investigate this phenomenon in an NGO environment. It investigates Australian overseas aid agencies’ responses to criticism of the relief effort following the Indian Ocean tsunami in 2004. It aims to determine whether voluntary annual report disclosures were reflective of impression management and/or of the discharge of functional accountability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 45 publications
(95 reference statements)
0
56
0
7
Order By: Relevance
“…Accountability to stakeholders, and to donors in particular, is crucial for all nonprofits—including CFs—that aim to build legitimacy and attract charitable contributions by providing signals of good housekeeping and by demonstrating their capacity to act in the interest of the community (Cabedo, Fuertes‐Fuertes, Maset‐Llaudes, & Tirado‐Beltrán, 2018; Conway, O'Keefe, & Hrasky, 2015; Levine Daniel & Eckerd, 2019; Murtaza, 2012). Given that nonprofits interact with a wide range of stakeholders who have varying information needs (Connolly, Hyndman, & McConville, 2013; Dhanani & Connolly, 2012), these organizations are expected to be accountable to multiple actors and on different aspects simultaneously (Ebrahim, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accountability to stakeholders, and to donors in particular, is crucial for all nonprofits—including CFs—that aim to build legitimacy and attract charitable contributions by providing signals of good housekeeping and by demonstrating their capacity to act in the interest of the community (Cabedo, Fuertes‐Fuertes, Maset‐Llaudes, & Tirado‐Beltrán, 2018; Conway, O'Keefe, & Hrasky, 2015; Levine Daniel & Eckerd, 2019; Murtaza, 2012). Given that nonprofits interact with a wide range of stakeholders who have varying information needs (Connolly, Hyndman, & McConville, 2013; Dhanani & Connolly, 2012), these organizations are expected to be accountable to multiple actors and on different aspects simultaneously (Ebrahim, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rendering account has become a highly salient issue for most NGOs including the necessity to become more transparent for their own social and environmental performance (Crespy and Miller 2011;Gugerty 2009;Manetti and Toccafondi 2014;Unerman and O'Dwyer 2010). Highly publicized scandals-bad lemon problemsapparent or real mission drifts and changing government relationships in the wave of new public management reforms have contributed to this (Conway et al 2015;Murtaza 2012;Schmitz et al 2012). In addition, NGOs have been quite active in lobbying for an improved social and environmental accountability of for-profits.…”
Section: Introduction and Research Questionmentioning
confidence: 99%
“…Insufficient transparency on the organizational level is still a relevant topic today. In their recent analyses of annual reports of NGOs Conway et al (2015), Dhanani and Connolly (2015) and Tremblay-Boire and Prakash (2015) found signs of unbalanced and weak accountability practices. Reports are too much focused on the user needs of powerful funders, influenced by media attention, sometimes misleading or more in line with an impression management than providing an overall, unbiased picture of NGOs performance.…”
Section: Introduction and Research Questionmentioning
confidence: 99%
“…Companies perceived as highly polluting are more likely to make legitimating disclosures (Clarkson et al, 2008;Cho et al, 2012). Significant media attention can provide a major legitimacy threat (Conway et al, 2015). Deepwater Horizon was hugely damaging to the environment and economy of the area affected and consequently BP plc, which suffered significant threats to its legitimacy from negative media coverage, vast reparatory fines (BP plc put aside $7.8bn to cover claims -BBC news online, 28/6/14), a record US criminal fine (BBC News Online, 15/11/12) and a lengthy ban on US federal contracts (BBC News Online, 13/8/13)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Neither statement portrays BP plc as agentive with reference to the spill; BP plc's role here is deleted or de-emphasised through grammatical structures. As a strategy for repairing legitimacy the effect here may be questionable, given that "lack of accountability can exacerbate a legitimacy gap" (Conway et al, 2015(Conway et al, , p.1079.…”
Section: Field -Angle Of Representationmentioning
confidence: 99%